PENGEMBANGAN MODUL KESETIMBANGAN KIMIA BERBASIS PENDEKATAN SAINTIFIK UNTUK KELAS XI SMA/MA - Yerimadesi, Yerimadesi; Bayharti, Bayharti; Handayani, Fitri; Legi, Wiwit Fitrah (Sainstek : Jurnal Sains dan Teknologi, 2016)
This developmental research aimed to produce scientific approach-based module in chemistry equilibrium topic, determine its validity, practicality, and effectiveness on grade XI students? learning outcome. It was based on 4-D development model that included defining, designing, and developing stage. Module was validated by expert and tested to senior high school (SMA) students. Research instruments used were questionnaire in the form of validity and practicality sheets and learning outcome test. Validity sheets were completed by 5 chemistry lecturers and 3 chemistry teachers. Practicality sheets were completed by 4 chemistry teachers and 25 grade XI students in public SMA (SMAN) 2 Batusangkar. Data were analyzed with Kappa Moment. The mean score of Kappa Moment for validity was 0.84 indicating a high degree of validity. The mean score of Kappa Moment for practicality were 0.87 (for students) and 0.84 (for teachers) indicating a very high degree of practicality. Effectiveness of the module was obtained from cognitive test score of students in SMAN 4 Padang. Analysis showed that the test score of students taught with module was siginificantly higher than that of students who were not. It can be concluded that the module developed was valid, practical, and effective for senior high school instruction.Key words: chemistry equilibrium, module, scientific approach.